Considering Carnegie's Legacy in the Time of Trump: A Science and Policy Agenda for Studying Social Class. (4th January 2019) - Williams, Wendy R.
Abstract: As one of the richest men in the world at a time of vast economic inequality, Andrew Carnegie published "The Gospel of Wealth" in 1889. In it, he delineated how wealth should be redistributed from the hands of the few to the many. Given SPSSI's 2018 conference location in Pittsburgh, and a similar concentration of wealth among a small group of White men today, it is an opportune time to consider the legacy of one of Pittsburgh's most famous citizens. Specifically, the comparison (and contrast) between Carnegie and President Trump provides an interesting backdrop for examining our present historical moment. Specifically, over the last 20 years, there has been renewed interest in studying social class among psychological researchers. Continuing with the conference theme of "building bridges, " this article will review the status of our knowledge about social class in order to provide a science and policy agenda for addressing poverty, wealth, and inequality in our time.